(untitled) (Desarrollo Económico. Revista de Ciencias Sociales, 2022)
This paper presents a reflection on monetary federalism, based on the history of the Argentinian complementary currencies (trueque). The first national trueque system (rgt, 1995-2000) is analysed as a form of monetary federalism, characterized by the decentralization of money-issuing and the uniqueness of the unit of account. This model has been challenged by two systems based on the centralization of money-issuing (rgt, 2001-2002 and rtzo, 2000-2002), but maintained its federal structure (rts, 2000-2002). I also argue that the crisis that threatened the trueque in 2002 reveals ethical and political implications of the ways in which creditos were issued.